2021
DOI: 10.1007/s13280-021-01664-1
|View full text |Cite
|
Sign up to set email alerts
|

How ecological research on human-dominated ecosystems incorporates agricultural and forestry practices: A literature analysis

Abstract: Understanding the nexus between practices and ecosystems is a critical challenge for sustainability, but it is unclear how ecological sciences have explored the question. To bring clarification, we conducted an analysis of ecology literature dealing with agricultural and forestry practices (AF practices), scanning a total of 27 556 references. Scientometric analyses showed that AF practices were addressed by 5.5% of ecology literature, and that this proportion increased from 2.5% to 8.1% between 1956 and 2017.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
1
1
0
Order By: Relevance
“…Yet, our results showed that only 5% of studies combine several spatial levels, while no studies from our sub-corpus addressed multiple temporal scales. This result echoes with other recent literature reviews that pointed to the lack of multi-level and spatiotemporal approaches in ecological research on human-dominated landscapes(Blanco et al 2022).Filling this gap in fostering multi-scalar PLSA would appear a key priority for future research given the valuable insights provided by the minority of studies that implemented this approach. For example, Karner et al (2019) conducted a multi-scalar participatory process to compare land sharing and land sparing approaches in Europe.…”
supporting
confidence: 76%
“…Yet, our results showed that only 5% of studies combine several spatial levels, while no studies from our sub-corpus addressed multiple temporal scales. This result echoes with other recent literature reviews that pointed to the lack of multi-level and spatiotemporal approaches in ecological research on human-dominated landscapes(Blanco et al 2022).Filling this gap in fostering multi-scalar PLSA would appear a key priority for future research given the valuable insights provided by the minority of studies that implemented this approach. For example, Karner et al (2019) conducted a multi-scalar participatory process to compare land sharing and land sparing approaches in Europe.…”
supporting
confidence: 76%
“…Therefore, it is possible to effectively promote the development of the forestry industry by studying and implementing management policies based on ecological intensification (Montesinos, 2019). At the same time, strengthening and deepening research on the ecological environment can also better guide forestry production practices (Blanco et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%